First Light in the Universe Saas-Fee Advanced Course 36. Swiss Society for Astrophysics and Astronomy - Loeb, Abraham; Ferrara, Andrea; Ellis, Richard S. (Saas-Fee Advanced Course, 2008)
The exploration of the first billion years of the history of the Universe, from the so-called Dark Ages to cosmic reionisation, represents one of the great challenges of contemporary astrophysics and one of the main drivers for future observational facilities. The book contains the elaborated notes of lectures given at the 36th Saas-Fee Advanced Course "First Light in the Universe" by three eminent scientists in the field: Abraham Loeb, Andrea Ferrara, and Richard Ellis. The formation of the first stars and black holes, the initial mass function, feedback effects, early dust formation, the history of cosmic star formation, distant galaxies, cosmic reionisation and the cosmic infrared background are the main topics treated. This book provides an accessible and up-to-date review of the field and will be useful to graduate students of astronomy, cosmologists, physicists and researchers.